Determination of fade margin for Ka band operating in equatorial region - Suhaimi, N.H.S; Badron, Khairayu; Ismail, Ahmad Fadzil; Ahmad, Yasser Asrul; Rahmat, M.H. (Faculty of Sciences and Technology of the University of El Oued (Algeria), 2018)
Reliability of satellite-Earth communication links can be improved by ensuring the availability of adequate fade margin. Fade margin can be established from prediction methods and also determined from quantitative analyses. Malaysia is located in the equatorial region, where Ka band link experiences high attenuation due to rain. Most existing prediction methods were developed in temperate climate region and therefore might not be applicable for conditions in Malaysia. In this paper, study on the effect of rain on Ka-band satellite signals has been carried out. Ka band transmissions operating at frequency of 20.199 GHz from the MEASAT 5 satellite are being monitored at MEASAT Cyberjaya ground station. It has been observed that rain attenuations experienced by the Ka band link vary from 6 to 34 dB. The determined fade margins for 99.97% availability, typical quality of service (QoS) standard for communications and 99.7% availability, conventional (QoS) criterion for broadcast are 34 dB and 27 dB respectively.